Effect of Interval between Neoadjuvant Chemoradiotherapy and Surgery on Oncological Outcome for Rectal Cancer: A Systematic Review and Meta-Analysis. (30th March 2016) - Wang, Xiao-Jie; Zheng, Zheng-Rong; Chi, Pan; Lin, Hui-Ming; Lu, Xing-Rong; Huang, Ying
Abstract : Aim . To evaluate the influence of interval between neoadjuvant chemoradiotherapy (NCRT) and surgery on oncological outcome. Methods . A systematic search was conducted in PubMed, the Cochrane Library, and Embase databases for publications reporting oncological outcomes of patients following rectal cancer surgery performed at different NCRT-surgery intervals. Relative risk (RR) of pathological complete response (pCR) among different intervals was pooled. Results . Fifteen retrospective cohort studies representing 4431 patients met the inclusion criteria. There was a significantly increased rate of pCR in patients treated with surgery followed 7 or 8 weeks later (RR, 1.45; 95% CI, 1.18–1.78; andP < 0.01 and RR, 1.49; 95% CI, 1.15–1.92; andP = 0.002, resp.). There is no consistent evidence of improved local control or overall survival with longer or shorter intervals. Conclusion . Performing surgery 7-8 weeks after the end of NCRT results in the highest chance of achieving pCR. For candidates of abdominoperineal resection before NCRT, these data support implementation of prolonging the interval after NCRT to optimize the chances of pCR and perhaps add to the possibility of ultimate organ preservation.